An Analytical Study of the Institutionalization and Consolidation of Prayer in Society Based on the Chronological Order of Quranic Surahs - Abdolhadi Feghhizadeh; Mojtaba Mohammadi Anviq; Farzad Dehghani (قرآن فرهنگ و تمدن)
Prayer (ṣalāh) is one of the most central ritual practices in Islam and a fundamental requirement of religious commitment. The Qur'an, throughout both the Meccan and Medinan periods, promotes prayer through a structured process aimed at gradually institutionalizing it within society. Observing the stages of promoting prayer-from its initial introduction in Mecca to its full establishment in Medina-reveals a clear model that can be utilized in educational and missionary contexts. This study, using a descriptive-analytical method and based on the chronological order of Quranic revelation, concludes that the Qur'an begins with individual-focused discourse, then progresses through familial and societal dimensions. It highlights the communal functions of prayer, addresses related challenges and impediments, and continues to emphasize its value and respond to adversarial propaganda even after its institutionalization. The research identifies five developmental stages in this process: 1- Introduction of prayer as a cognitive-ethical and ritual practice; 2- Promotion of prayer culture on individual and societal levels; 3- Establishment of discourse and functionalism centered around prayer; 4- Religious and ethical nation-building through prayer; 5- Diagnosis and resolution of challenges facing the religious community and prayer observance.The first stage began early in the Meccan period, followed by the stages of cultural promotion and discourse in the middle and later parts of the same period. Nation-building was initiated during the transition to Medina and was emphasized in the early Medinan period. Finally, during the late Medinan period, the Qur'an presented a detailed stage of diagnostic and corrective engagement, affirming the consolidation of the upright religion with prayer at its core.